Penegakan Kode Etik Profesi Kepolisian - Melaniati Suharni; Kalistus Gaudensius Wayong Huler; Bernadus Febryanto; Dwityas Witarti Rabawati (Pusat Riset dan Inovasi Nasional, 2024)
The legal profession is one of the professions that demands the fulfillment of moral values from its development. The main benchmark for being an organizer of the legal profession in enforcing the law lies in the independence of professional organizers and strong moral integrity when facing various problems that are their responsibility. To be a good organizer of the legal profession in carrying out its professional duties in enforcing the law, practitioners who have qualified attitudes, humanitarian attitudes, attitudes of justice, are able to see and place objective values in a case handled, an honest attitude, and have technical skills and ethical maturity. The code of ethics of the legal profession actually functions as an ethical controller for those who carry out the legal profession. With legal professional ethics, it is expected that legal professionals have certain critical individual abilities.The National Police as one of the legal profession that deals directly with the community so that content is needed related to the standards of behavior and actions that are observed, where the Code of Professional Ethics of the National Police of the Republic of Indonesia is basically a guide for all actors of police functions in carrying out their duties in accordance with the laws and regulations in force in their territory contained in POLRI Regulation No. 7 of 2022 concerning the Code of Professional Ethics and Commission on the Code of Ethics of the National Police of the Republic of Indonesia. However, it is undeniable that there are still many violations of the code of ethics that often occur and are committed by police officers which result in low or decreased integrity of the police in the eyes of the public.